The Ortles ice cores: uncovering an extended climate archive from the Eastern Alps - DREOSSI, GIULIANO; BARBANTE, Carlo; BERTÒ, MICHELE; GABRIELI, Jacopo; Spolaor, Andrea; STENNI, Barbara; Carturan, Luca; De Blasi, Fabrizio; Seppi, Roberto; Zanoner, Thomas (Geophysical Research Abstracts, 2017)
During the last half century, oxygen and hydrogen stable isotope content of ice cores has been extensively used for air temperature reconstructions. The most suitable glaciers of the Alpine area, most exclusively in the Western Alps, havebeen utilizedfor icecoring formore thanfour decades.The paleoclimatic potential of theEastern Alps isstilllargelyunexploitedandwasscarcelyutilizedinthepastmainlybecauseofthelowerelevation(comparedto Western Alps) and hence the difﬁculty to ﬁnd glaciers in cold conditions. The warming temperature trend appears to be particularly pronounced in the Alps, threatening the preservation of the glaciated areas and creating a sense of urgency in retrieving climatic archives before it is too late. In autumn 2011, four deep cores were drilled on Mt Ortles, South Tyrol, Italy, at 3859 m a.s.l. An extensive reconstructed temperature record for the Ortles summit, based on the surrounding meteorological station data, is available for the last 150 years, while an automatic weather station had been operating from 2011 to 2015 in proximity of the drilling site. The new ice core chronology, based on 210Pb, tritium, beta emissions analysis and 14C measurements of the particulate organic carbon, indicates that the bottom ice is 7000 years old, making it the second most extended glaciological archive ever retrieved in the Alps. The three equally long ice cores have been analyzed for oxygen and hydrogen stable isotopes throughout their length, and the goal is to create an Ortles stacked record for d18O and dD and compare the isotopic data to instrumental temperatures and to other Alpine records. Since 2008, several snow pits were dug in proximity of the drilling site during summer, when the temperature can oftenexceedthemeltingpoint.Theisotopicproﬁlesofthe2015snowpit,dugattheendofanexceptionallywarm summer,showhowtheisotopesignalisnowaffectedbythepost-depositionalprocessesthathaveoccurredduring that summer.